Automated targeting technique for indirect inter-plant hydrogen integration - W.M. Shehata (Egyptian Journal of Petroleum)
The increase of hydrogen demand has been one of the focal point recently. Indirect inter-plant hydrogen integration (IPHI) is a new issue for reducing hydrogen consumption and hydrogen discharge, in which hydrogen networks for different plants are integrated indirectly through centralized partitioning regeneration unit where hydrogen is regenerated for further reuse/recycle. This work is an extension of the automated targeting technique that was developed for single hydrogen network and the automated targeting that was developed for inter-plant water integration. The concentration cascade model has been developed to optimize hydrogen networks through partitioning regeneration unit such as pressure swing adsorption (PSA) or membrane separation. Two case studies from literature are studied to illustrate the applicability of the proposed model.